The validity of the patient health Questionnaire-9 to screen for depression in patients with type-2 diabetes mellitus in non-communicable diseases clinics in Malawi - Udedi, Michael; Muula, Adamson S.; Stewart, Robert C.; Pence, Brian W. (BMC psychiatry, 2019)
Background Depression is a global problem, affecting populations worldwide, but is too often under-diagnosed. The identification of depression among patients with diabetes is important because depression is prevalent in this group and can complicate diabetes management. Objectives The aim of the study was to determine the sensitivity and specificity of the PHQ-9 in the detection of depression among patients with type-2 diabetes mellitus attending non-communicable diseases (NCD) clinics in Malawi. Methods We conducted a validation study of the Patient Health Questionnaire (PHQ-9) among 323 patients with type-2 diabetes mellitus who attended two NCD clinics in one of the 28 districts of Malawi. The participants were screened consecutively using the nine-item PHQ-9 in Chichewa by a research assistant and completed a diagnostic interview using the Structured Clinical Interview for DSM-IV (SCID) for depression with a mental health clinician. We evaluated both content validity based on expert judgement and criterion validity of the Patient Health Questionnaire (PHQ-9) based on performance against the SCID. The PHQ-9 cutpoint that maximized sensitivity plus specificity was selected to report test characteristics. Results Using the SCID for depression, the prevalence of minor or major depression was 41% (133/323). The internal consistency estimate for the PHQ-9 was 0.83, with an area under the receiver operator curve (AUC) of 0.93 (95% CI, [0.91–0.96]). Using the optimal cut-point of ≥9, the PHQ-9 had a sensitivity of 64% and a specificity of 94% in detecting both minor and major depression, with likelihood ratio-positive = 10.1 and likelihood ratio negative =0.4 as well as overall correct classification (OCC) rate of 81%. Conclusions This is the first validation study of the PHQ-9 in NCD clinics in Malawi. Depression was highly prevalent in this sample. The PHQ-9 demonstrated reasonable accuracy in identifying cases of depression and is a useful screening tool in this setting. Health care workers in NCD clinics can use the PHQ-9 to identify depression among their patients with those having a positive screen followed up by additional diagnostic assessment to confirm diagnosis. Trial registration PACTR201807135104799 . Retrospectively registered on 12 July 2018.